Noted: Frontline humour takes on generals - Violet Cho (Asia Pacific Network, 2009)
This is is a new political cartoon collection by Burmese artist and cartoonist Harn Lay. It is a revealing insight into Burma—where political resistance and traditional art and performance meet. The book demonstrates and is part of the ongoing resistance to an unjust abuse of power. Lay portrays key issues such as political prisoners, extended house arrest of pro-democracy icon Aung San Suu Kyi, the military’s response to sanctions, Burma-ASEAN relations and business deals with neighbouring countries.